If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -2(x + -5) + -7 + 5x = 21 + 3x Reorder the terms: 8x + -2(-5 + x) + -7 + 5x = 21 + 3x 8x + (-5 * -2 + x * -2) + -7 + 5x = 21 + 3x 8x + (10 + -2x) + -7 + 5x = 21 + 3x Reorder the terms: 10 + -7 + 8x + -2x + 5x = 21 + 3x Combine like terms: 10 + -7 = 3 3 + 8x + -2x + 5x = 21 + 3x Combine like terms: 8x + -2x = 6x 3 + 6x + 5x = 21 + 3x Combine like terms: 6x + 5x = 11x 3 + 11x = 21 + 3x Solving 3 + 11x = 21 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 3 + 11x + -3x = 21 + 3x + -3x Combine like terms: 11x + -3x = 8x 3 + 8x = 21 + 3x + -3x Combine like terms: 3x + -3x = 0 3 + 8x = 21 + 0 3 + 8x = 21 Add '-3' to each side of the equation. 3 + -3 + 8x = 21 + -3 Combine like terms: 3 + -3 = 0 0 + 8x = 21 + -3 8x = 21 + -3 Combine like terms: 21 + -3 = 18 8x = 18 Divide each side by '8'. x = 2.25 Simplifying x = 2.25
| -3+4x-7x=21 | | 118=4(20)+38 | | 8d-3/5=5d+3/2 | | 51=2x+7x+6 | | p=23/3(18) | | 106/5=7x+4x-4/5 | | p=7(18) | | 10x+7=20x | | p=6(18) | | 6a-4a-5=7a-23 | | -7x+6x=-2 | | (7u-4v-2)(2u+1)=0 | | x+10=9-1 | | -2x-2-2x=26 | | Y=50.8y | | p=5(18) | | Y=50+8y | | 46=4x+38 | | -2=5x-x-2 | | 3=-2x+6x+7 | | p=44/9(20) | | p=44/9(18) | | -89=6x+2x-9 | | 2/5+2x=-28/5 | | 12-12z=-9-10 | | p-36=44/9(h-6) | | 18u^6-8u^4/2u^3 | | h=-16t^2+64t+720 | | Z=12 | | 25+24z=25+25z | | 60x-0.2x^2=p(x) | | 45+9y=90 |